2021
DOI: 10.1080/07391102.2020.1869588
|View full text |Cite
|
Sign up to set email alerts
|

Withanolides from Withania somnifera as an immunity booster and their therapeutic options against COVID-19

Abstract: Traditionally, Withania somnifera is widely used as an immune booster, anti-viral, and for multiple medicinal purposes. The present study investigated the withanolides as an immune booster and antiviral agents against the coronavirus-19. Withanolides from Withania somnifera were retrieved from the open-source database, their targets were predicted using DIGEP-Pred, and the protein-protein interaction was evaluated. The drug-likeness score and intestinal absorptivity of each compound were also predicted. The ne… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 51 publications
0
33
0
Order By: Relevance
“…In one study, withanolide Q was predicted to modulate the highest number of proteins, showed positive human intestinal absorption, and had the highest drug-likeness score. Similarly, withanolide D and withanolide G were predicted to have better binding affinity with SARS-CoV-2 papain-like cysteine protease (PL pro ), withanolide M with M pro , and withanolide M with spike protein based on binding energy and the number of hydrogen bond interactions [ 44 ]. In the present study, withanone (−7.7 (kcal/mol) against RBD), withanolide A (−8.6 (kcal/mol) against M pro ), and withanolide G (−7.4 (kcal/mol) against RBD) showed the best binding affinity to receptors among the withanolides ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…In one study, withanolide Q was predicted to modulate the highest number of proteins, showed positive human intestinal absorption, and had the highest drug-likeness score. Similarly, withanolide D and withanolide G were predicted to have better binding affinity with SARS-CoV-2 papain-like cysteine protease (PL pro ), withanolide M with M pro , and withanolide M with spike protein based on binding energy and the number of hydrogen bond interactions [ 44 ]. In the present study, withanone (−7.7 (kcal/mol) against RBD), withanolide A (−8.6 (kcal/mol) against M pro ), and withanolide G (−7.4 (kcal/mol) against RBD) showed the best binding affinity to receptors among the withanolides ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…PI3K activates immunity by up-regulating IL-10 and inhibiting proinflammatory cytokines, possibly through the regulation of Rac1 protein (162). Withanolides, as immunopotentiators and antiviral agents against COVID -19, may play a role by targeting the Rac1 protein (163). Compared with Rac1 WT, melanoma cells with Rac1(P29S) mutations express high levels of PD-L1 and therefore have the ability to evade immune surveillance (164).…”
Section: Rac1 Participates In Tumor Microenvironment-mediated Immune Escapementioning
confidence: 99%
“…A study carried out by our team predicted the potential of withacoagin and withanolide B to block viral spike protein and RdRp enzyme with a high binding affinity (Borse et al, 2020). Moreover, many recent virtual screening studies reported the potential of withanolides to inhibit SARS-CoV-2 proteins with a high binding affinity (Khanal et al, 2021) (Srivastava et al, 2020) (Parida et al, 2020) (Shree et al, 2020) (Tripathi. M. K. et al, 2020) (Chikhale et al, 2020).…”
Section: Introductionmentioning
confidence: 99%